Regulation of COVID-19 fake news infodemic in China and India. (November 2020) - Rodrigues, Usha M; Xu, Jian
During the recent outbreak of coronavirus, the concern about proliferation of misleading information, rumours and myths has caused governments across the world to institute various interventionist steps to stem their flow. Each government has had to balance the dichotomy between freedom of expression and people's right to be safe from the adverse impact of inaccurate information. Governments across the world have implemented a number of strategies to manage COVID-19 including issuing public advisories, advertising campaigns, holding press conferences and instituting punitive regulations to combat the distribution of false and misleading information. We examine the two most populous countries' governments' response to the scourge of fake news during COVID-19. China and India are the most challenging nations to govern in terms of their sheer size and diversity of their population. Each country's government has taken several steps to minimise the impact of fake news during COVID, within its own political system.